(untitled) (Pedagogy of Higher and Secondary Education, 2021)
The need to study MathCAD and the settlement and graphic work on the topic «Mathematical package MathCAD». Served example problem for settlement and graphic work in computer science for students of mechanical skills. This work will enable to implement interdisciplinary links courses «Informatics», «Higher Mathematics» and «Strengh of Materials».